On the origin of new genes in Drosophila - Zhou, Qi; Zhang, Guojie; Zhang, Yue; Xu, Shiyu; Zhao, Ruoping; Zhan, Zubing; Li, Xin; Ding, Yun; Yang, Shuang; Wang, Wen (Genome Research, 2008)
Several mechanisms have been proposed to account for the origination of new genes. Despite extensive case studies, the general principles governing this fundamental process are still unclear at the whole-genome level. Here, we unveil genome-wide patterns for the mutational mechanisms leading to new genes and their subsequent lineage-specific evolution at different time nodes in the Drosophila melanogaster species subgroup. We find that (1) tandem gene duplication has generated ∼80% of the nascent duplicates that are limited to single species (D. melanogaster or Drosophila yakuba); (2) the most abundant new genes shared by multiple species (44.1%) are dispersed duplicates, and are more likely to be retained and be functional; (3) de novo gene origination from noncoding sequences plays an unexpectedly important role during the origin of new genes, and is responsible for 11.9% of the new genes; (4) retroposition is also an important mechanism, and had generated ∼10% of the new genes; (5) ∼30% of the new genes in the D. melanogaster species complex recruited various genomic sequences and formed chimeric gene structures, suggesting structure innovation as an important way to help fixation of new genes; and (6) the rate of the origin of new functional genes is estimated to be five to 11 genes per million years in the D. melanogaster subgroup. Finally, we survey gene frequencies among 19 globally derived strains for D. melanogaster-specific new genes and reveal that 44.4% of them show copy number polymorphisms within a population. In conclusion, we provide a panoramic picture for the origin of new genes in Drosophila species.
10.1101/gr.076588.108